Binocular coordination of saccades: development, aging and cerebral substrate - Zoë Kapoula; Marine Vernet; Qing Yang; Maria Pia Bucci (Journal of Eye Movement Research)
The origin of binocular coordination of saccades (central, peripheral) and the role of learning remain controversial (Hering vs Helmholtz). We will present evidence for learning: in young children (5 years) horizontal saccades are poorly yoked, coordination improves slowly with age particularly at near viewing distances. In dyslexic teenagers coordination of horizontal saccades is poor relative to non-dyslexics, suggesting slower learning. On the other hand, in healthy elderly participants (73 years) coordination of vertical saccades is intact, an example of a non ageing sub-system. To assess further central mechanisms, we applied TMS over the posterior parietal cortex of healthy adults, 100 ms after target onset. TMS impaired coordination particularly for rightward and downward saccades. Thus binocular coordination of saccades relies partially on cerebral function.experimental stages.